Membrane glucocorticoid receptors are down regulated by glucocorticoids in patients with systemic lupus erythematosus and use a caveolin-1-independent expression pathway. Issue 9 (31st January 2006) - Spies, C M; Schaumann, D H S; Berki, T; Mayer, K; Jakstadt, M; Huscher, D; Wunder, C; Burmester, G-R; Radbruch, A; Lauster, R; Scheffold, A; Buttgereit, F
Abstract : Background: Membrane-bound glucocorticoid receptors (mGCR) are up regulated on monocytes after in vitro stimulation and in patients with rheumatoid arthritis. Caveolin-1 is critical for the transport of plasma membrane oestrogen receptors to the cell surface. Objectives: To investigate the expression of mGCR in patients with systemic lupus erythematosus (SLE)—a disease with different aetiopathogenesis and treatment regimens—and to examine whether caveolin-1 is critical for the transport of mGCR to the cell surface. Methods: Frequencies of mGCR+ peripheral blood mononuclear cells were measured using high-sensitivity immunofluorescent staining and tested for correlation with SLE disease activity and glucocorticoid treatment. Semiquantitative polymerase chain reaction, immunofluorescence, recombinant expression and confocal laser-scanning microscopy were used to search for an association of mGCR with caveolin-1. Results: The frequencies of mGCR+ monocytes (CD14+) were considerably higher in patients with SLE (n = 33) than in healthy controls (n = 58), whereas B cells (CD19+) were not different in this regard. T cells (CD3+) were always mGCR−. The frequency of mGCR+ monocytes in patients with SLE did not correlate with disease activity, but did inversely correlate with glucocorticoid dosages; this inverse correlation was confirmed by corresponding in vitro experiments with stimulated monocytes. The induced up regulation of mGCR was not accompanied by an up regulation of caveolin-1, and mGCR are not colocalised with caveolin-1 in plasma membrane caveolae. Conclusion: mGCR are (a) up regulated in patients with SLE and by inflammatory stimuli and (b) down regulated by glucocorticoids, suggesting a negative feedback loop to control glucocorticoid action. Drugs binding selectively to mGCR may in future prove to be of therapeutic value.